Oral Health Outcome Measures: A Feasibility Evaluation - Yrjänä Hynninen; Samuli Voltti; Markus Sormunen; Annamari Nihtilä; Päivi Siukosaari; Lari Koukkula; Riikka-Leena Leskelä (Elsevier, 2023)
Objectives: Outcomes of oral health care must be measured and analysed to improve oral health care delivery, outcomes, and quality. This study aims to develop and test outcome measures for the needs of oral health organisers and explore their feasibility using clinical data. Methods: Based on the literature review and oral health advisory board, outcome measures for oral health care were identified, developed, and tested. Data from 425,000 clinical examinations were obtained from the clinical records of 8 public oral care providers in Finland. Results: The advisory board selected 7 outcome measures: 1 on oral self-care, 2 on periodontitis, 3 on caries, and 1 on missing teeth. A large variation was found in the diagnostic and data entry practices of these outcome measures. The coverage of caries and missing teeth entries was good, but the quality of initial and remineralised caries entries was questionable. The caries and missing teeth measures show statistically significant differences amongst some providers. Conclusions: The measures "new cavitated caries surfaces," "cavity-free clinical examinations," and "the change in the missing value" were evaluated as feasible. The results of these measures provided insight about the effectiveness of oral care and enabled the comparison between the providers and age groups. Statistically significant differences between the providers in the measures imply potential possibilities for providers to learn from each other.